Without Straying from Philosophical Origins and the Reality of Life. Interview with Eglė Rimkutė - Almonaitienė, Junona S. (Psichologija, 2022)
Interview of Junona Almonaitienė, a graduate of Vilnius University, with associate professor Eglė Rimkutė, a teacher and researcher at the same university from 1966 till 2006, who’s carrier was mainly related to cognitive psychology and methodology of psychology. The interview reveals her subjective approach to various methodological problems of psychology, the nature and shifts of the approach, and her personal efforts to develop a more comprehensive, realistic, sociocultural psychology. As the interlocutors practically collaborated in planning and discussing research during one of the time periods covered here, the subjective experiences of both, related to local as well as more general methodological problems in psychology, are analyzed retrospectively. The entire interview can be seen as a practical effort of writing a microhistory.